Expression of extracellular matrix proteins in cervical squamous cell carcinoma--a clinicopathological study. Issue 10 (October 1998) - Goldberg, I; Davidson, B; Lerner-Geva, L; Gotlieb, W H; Ben-Baruch, G; Novikov, I; Kopolovic, J
Abstract : AIM: To evaluate the intracellular and peritumoral expression of matrix proteins in squamous cell carcinoma of the uterine cervix using immunohistochemistry. METHODS: 71 squamous cell carcinomas and 10 controls were stained for laminin, fibronectin, and collagen IV. Cytoplasmic staining in tumour cells and peritumoral deposition of matrix proteins were evaluated. The association between staining results and patient age, tumour stage, histological grade, and survival was studied. RESULTS: Positive cytoplasmic staining for laminin, fibronectin, and collagen IV was observed in 17 (23.9%), 27 (38%), and 10 (14.1%) cases, respectively. Staining for laminin was most pronounced in the invasive front of tumour islands, while for fibronectin and collagen IV it appeared to be diffuse. Peritumoral staining for laminin and collagen IV was detected in 12 cases (16.9%). Early stage (Ia1-Ia2) tumours were uniformly negative for all three proteins. Cytoplasmic staining for laminin correlated with positive staining for fibronectin and collagen IV, and with the presence of a peritumoral deposition of collagen IV and laminin. There was no correlation with any of the three markers between staining results and patient age, stage, grade, or survival. CONCLUSIONS: Expression of extracellular matrix proteins in some cervical squamous cell carcinomas might reflect the enhanced ability of these tumours to modify the peritumoral stroma. This ability seems to be absent in early stage tumours. The correlation between intracytoplasmic and peritumoral expression of matrix proteins supports the evidence of their synthesis by tumour cells. However, this property did not correlate with disease outcome in this study.